Social and Environmental Determinants of Diarrheal Diseases among Children under Five Years in Epworth Township, Harare - Sandra Chari; Thokozani Patrick Mbonane; Renay Helouise Van Wyk (MDPI AG, 2023)
Children five years or younger in low- and middle-income countries (LMICs) are severely affected by diarrheal disease, especially in the sub-Saharan region. Hence, this study aimed at determining the prevalence and determinants of diarrhoea disease among children under 5 years in Epworth Township, Zimbabwe. A descriptive cross-sectional study was conducted at a local clinic in Epworth Township, Harare. A convenience sampling strategy was used to recruit study participants for participation, and 386 children were enrolled in the study. The majority were male children (n = 229; 59.3%), whereas there were more female caregivers (n = 370; 95.9%) than male caregivers (n = 16; 4.1%). The prevalence of diarrhoea disease in the study was 25.1%. The determinants associated with diarrhoea were being partially vaccinated (AOR 2.38, CI: 95% 2.80-8.22), collecting water more than 1 kilometre from a household (AOR 4.55; CI: 95% 2.10-9.85), and using untreated water (AOR 6.22; CI: 95% 2.13-18.20). The age of the caregiver (being older than 21) and using a clean water container (AOR 0.05; CI: 95% 0.02-0.13) were protective factors. Provision of primary health care, especially the prevention of a disease through immunization and rendering environmental health services, could reduce the prevalence of diarrhoea in disadvantaged townships.